Effect of reduced nitrogen fertilization and nitrogen topdressing on physiological traits of buckwheat - WU Xinyang; LU Jiahao; WANG Caiqin; MA Hongmei; WU Zhiming (Guan'gai paishui xuebao)
【Objective】 Overuse of nitrogen fertilizer is a major source of nonpoint pollution in agricultural production. Reducing nitrogen application and improving nitrogen use efficiency are essential for developing sustainable agriculture. We investigate in this paper the impact of reduced nitrogen fertilization and nitrogen topdressing on physiological traits of buckwheat. 【Method】 The field experiment consisted of six nitrogen fertilizations: applying 100 kg/hm2 of nitrogen as base fertilizer (CK1), applying 70 kg/hm2 of nitrogen as base fertilizer and 30 kg/hm2 of nitrogen for topdressing (CK2), applying 70 kg/hm2 of nitrogen as base fertilizer and 0.25 kg/hm2 of nitrogen in dissolved urea (concentration 1%) for spray-topdressing (CK3), applying 70 kg/hm2 of nitrogen as base fertilizer and 0.25 kg/hm2 of nitrogen in dissolved urea (1% concentration) for spray-topdressing using UAV (T4), applying 70 kg/hm2 of nitrogen as base fertilizer and 0.5 kg/hm2 of nitrogen in dissolved urea (concentration 2%) for spray-topdressing using UAV (T5), applying 70 kg/hm2 of nitrogen as base fertilizer and 1 kg/hm2 of nitrogen in dissolved urea (concentration 4%) for spray-topdressing using UAV (T5). In each treatment, we measured dry matter accumulation, photosynthetic traits, and antioxidant enzyme activity of the crop. 【Result】 ① Aboveground dry matter accumulation increased over time, with the accumulation rate initially increasing and then declining. At the maturity stage, T5 had the highest dry matter accumulation, surpassing other treatments by 16.03%-82.88% in total accumulation and 34.05%-132.05% in accumulation rate. ② Chlorophyll content and net photosynthetic rate varied with treatments, with T5 showing the highest values at maturity stage and CK1 the lowest. ③ Antioxidant enzyme activity exhibited a single-peak trend as the crop matured. At the post-bloom stage, T5 increased superoxide dismutase activity by 1.16%-19.16%, peroxidase activity by 0.49%-35.49%, and catalase activity by 11.89%-51.76%, compared to other treatments, while antioxidant activity in T4 and T5 was comparable. Malondialdehyde content increased with leaf senescence, but their values in T4 and T5 were similar at the maturity stage, 10.99%-19.00% lower than that in other treatments. ④ Compared to other treatments, T5 significantly increased grain number, grain weight per plant, and 1 000-grain weight by 9.65%-80.67%, 5.15%-59.17%, and 9.77%-17.01%, respectively, resulting in a yield increase of 21.66%-140.30%. 【Conclusion】 Applying 70 kg/hm2 of nitrogen as a basal fertilizer combined with a 1%-2% urea solution applied via UAV for foliar spraying is the optimal nitrogen fertilization strategy for buckwheat; it increases dry matter accumulation, enhances antioxidant enzyme activity, prolonges leaf functionality, and improvs photosynthetic efficiency, thereby boosting crop yield.